Financial constraints, factor combination and Gibrat's law in Africa - (:unkn) unknown (My University, 2019)
This paper investigates the validity of Gibrat's law in sub-Saharan Africa using data from 22,495 firms operating in 45 African countries. Results indicate that Gibrat's law does not hold in Africa, i.e. small firms create more jobs than their larger counterparts do. We point out that the usual explanations (such as diminishing returns, the learning process, and the minimum efficient size) do not explain this finding. We present a new explanation based on firm access to capital. According to our hypothesis, employment growth among small firms in Africa is faster because small firms adopt labor-intensive and capital-saving technology to expand their business activities. SMEs have a lower capital-labor factor because in order to grow, they tend to overuse labor and underuse capital due to financial constraints., hence their greater job growth momentum. Different econometric tests provide support to our hypothesis. Specifically, we prove that the negative relationship between firm size and growth is mitigated for firms with access to credit.
Keywords: African Research